Analysis of the Influential Factors on the Performance of the Civil Service Police Unit in Pulogadung District East Jakarta (Global Journal of Management and Business Research, 2019)
This study intends to examine the factors that influence the performance of the civil service police unit. This research approach is descriptive associative with sampling using a census. Sampling was carried out at the Pramong Praja Police in the Pulo Gadung District of East Jakarta. The method of data analysis uses Structural Equation Modeling -Partial Least Square (SEM-PLS) using Smart PLS software version 3. The test results show human resources, facilities, and communication have a positive and insignificant effect on the performance of the Civil Service Police Unit.
Keywords: performance; public sector